2018
DOI: 10.4236/oalib.1104440
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Nutrients Limiting Sustainable Potato Production in the Highlands of South-Western Uganda

Abstract: Soil fertility management is one of the major strategies for improving potato productivity in the highlands of southwestern Uganda. Land belonging to potato farmers is highly fragmented hindering sustainable potato production under smallholder farming systems. Land fragmentation brings a major challenge to small-scale farmers in soil fertility management, increasing costs of production. However, identifying major soil nutrients limiting potato production in the highlands of southwestern Uganda is an avenue of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…The soil pH in the country is low, contributing further to P adsorption and to the unavailability of other key nutrients (Mugo et al., 2020). High soil erosion and nutrient leaching further aggravate soil fertility problems in the highlands (Ministry of Environment & Natural Resources, 2016; Muchena & Gachene, 1988; Muzira et al., 2018; Nyawade et al., 2018). Continuous farming for many years has also been linked to declining soil fertility (Willy et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil pH in the country is low, contributing further to P adsorption and to the unavailability of other key nutrients (Mugo et al., 2020). High soil erosion and nutrient leaching further aggravate soil fertility problems in the highlands (Ministry of Environment & Natural Resources, 2016; Muchena & Gachene, 1988; Muzira et al., 2018; Nyawade et al., 2018). Continuous farming for many years has also been linked to declining soil fertility (Willy et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 41 kg N ha −1 , 4 kg P ha −1 , and 31 kg K ha −1 is mined from soil in East Africa and that this has led to negative nutrient balances (Bekunda et al, 2002). In recent studies, N, P, S, and B were found to limit potato production (Kenya Soil Survey, 2014;Mugo et al, 2020EATA, 2014Muzira et al, 2018). Fertilizer management in the region is thus key for sustainable crop production.…”
Section: Introductionmentioning
confidence: 99%
“…Entre fitopatógenos encontramos aquellos de origen bacteriano como Ralstonia solanacearum, que produce marchitez y atrofiamiento de la planta. Esta enfermedad es catalogada como la segunda en importancia por su capacidad para limitar la producción de papa, causando elevadas pérdidas al año (Muzira et al, 2018).…”
Section: Discussionunclassified
“…Regrettably, agricultural food production is constrained by reduced soil fertility that threatens the livelihoods of most farmers in Uganda [13]. Accelerated soil fertility reduction under the current land use in Uganda contributes to many soil management problems, including soil acidity.…”
Section: Introductionmentioning
confidence: 99%